RUNNING UP THAT HILL - Italian civic addresses and the quest for accuracy - Zunino, Valerio (GEOmedia, 2018)
The quality of toponymy data has come increasingly under the microscope in recent years. These augmentations infiltrating the sector now require extremely accurate, up-to-date and comprehensive data, most crucially in respect of, for example, the automatic driving project, emergency services, and applications inherent in civil protection. STUDIO SIT Srl was conceived of in 1991, the dim and distant past for many. For suppliers such as HERE and TOMTOM involved with the surveying and mapping of Italian civic numbering, the Ligurian company has been able to exceed a 95% degree of accuracy, completeness and updating, unique in this country, which traditionally lacks the availability of good quality toponymy opendata.